PERBEDAAN LUARAN MATERNAL ANTARA IBU PREEKLAMSIA BERAT DENGAN DAN TANPA SINDROM HELLP DI RSUP DR. M.DJAMIL PADANG - Mufiidah, Muthia; Defrin, Defrin; Rusjdi, Selfi Renita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Background: Preeclampsia is a new onset of hypertensive disorder that occurs after 20 weeks of gestation. Based on the degree of severity, preeclampsia is divided into two categories: mild preeclampsia and severe preeclampsia. Patients with severe preeclampsia can have some complications, one of them is HELLP syndrome (haemolysis, elevated liver enzymes, low platelet count). HELLP syndrome can further affect maternal mortality and morbidity rates. Objective: This study aims to determine whether there are differences in maternal outcomes in severe preeclampsia with HELLP syndrome and severe preeclampsia without HELLP syndrome. Methods: The type of this research is observational analytic with a case-control approach using data from medical records. This research was conducted in July 2022–January 2023 at Dr. M. Djamil Padang Hospital. The samples were selected using simple random sampling technique and obtained a total of 78 samples. obtained. Bivariate analysis in this study was conducted using Chi-square test. Results: Patients with severe preeclampsia with and without HELLP syndrome were dominated by the low risk age group (20-35 years). Based on the number of pregnancies, the highest frequency was found in the multigravida group. The results of blood pressure and urine protein measurements in the two subjects were not much different. LDH and SGPT levels increased and platelet count decreased in severe preeclampsia with HELLP syndrome. Conclusion: There was no significant difference between the maternal outcomes in severe preeclampsia with HELLP syndrome and severe preeclampsia without HELLP syndrome (p>0.05)